1995
DOI: 10.1007/bf00018310
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional properties of the coleoptile chloroplast: Photosynthesis and photosensory transduction

Abstract: Recent studies have shown that guard cell and coleoptile chloroplasts appear to be involved in blue light photoreception during blue light-dependent stomatal opening and phototropic bending. The guard cell chloroplast has been studied in detail but the coleoptile chloroplast is poorly understood. The present study was aimed at the characterization of the corn coleoptile chloroplast, and its comparison with mesophyll and guard cell chloroplasts. Coleoptile chloroplasts operated the xanthophyll cycle, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…1 A–D). Similar to our results, zeaxanthin has been found to participate in photosensory transduction and protect the chloroplasts in the coleoptile ( Zhu, Zeiger, & Zeiger, 1995 ). Tang et al (2021) found that exogenous zeaxanthin pretreatment maintained a higher photosystem process and fresh weight of pepper seedlings than the control during low temperatures.…”
Section: Discussionsupporting
confidence: 91%
“…1 A–D). Similar to our results, zeaxanthin has been found to participate in photosensory transduction and protect the chloroplasts in the coleoptile ( Zhu, Zeiger, & Zeiger, 1995 ). Tang et al (2021) found that exogenous zeaxanthin pretreatment maintained a higher photosystem process and fresh weight of pepper seedlings than the control during low temperatures.…”
Section: Discussionsupporting
confidence: 91%
“…Light-grown corn coleoptiles have functional chloroplasts (19) and show chlorophyll a fluorescence transients similar to those obtained from guard cell chloroplasts (data not shown). We investigated whether blue light can enhance the red light-stimulated fluorescence quenching from coleoptile chloroplasts, in a response homologous to that observed with guard cell chloroplasts.…”
Section: Methodssupporting
confidence: 60%
“…A recent study has characterized photosynthetic properties of corn coleoptile chloroplasts which contrast with those from corn mesophyll and are strikingly similar to the properties of guard cell chloroplasts (19). These properties include high rates of photosystem II-dependent oxygen evolution, low rates of carbon fixation, a large starch content, and a xanthophyll cycle which is highly sensitive to low fluence rates of incident radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role as an environmental sensor (Outlaw et al. , 1981), emerging data point to the guard cell chloroplast as an evolutionary repository specialized for integrated signal transduction to regulate stomatal aperture in a variety of developmental, environmental and physiological circumstances (Zhu et al. , 1995; Quinones et al.…”
Section: Discussionmentioning
confidence: 99%